2012
DOI: 10.1177/0748233712462475
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of titanium oxide nanoparticles causes functionality and DNA damage in buffalo (Bubalus bubalis) sperm in vitro

Abstract: The present study has examined the effect of different concentrations (1 μg/ml, 10 μg/ml and 100 μg/ml) of titanium oxide (TiO2) nanoparticles (NPs) (<100 nm) on viability, membrane integrity, capacitation status and DNA integrity of buffalo spermatozoa. Characterization of NPs was done by the transmission electron microscopy (TEM) and dynamic light scattering (DLS). Sperm chromatin dispersion (SCD) test and acridine orange test (AOT) were employed to detect DNA fragmentation in sperm treated with NPs. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 68 publications
(64 reference statements)
0
25
0
Order By: Relevance
“…Nanoparticles used in this sector potentiate fertilization efficiency that facilitates fertilization of more females from a single collection. It had some limitation such as; to be developed it needs biomarker library and restrictions of purebred on artificial insemination [155].…”
Section: Sperm Nanopurificationmentioning
confidence: 99%
“…Nanoparticles used in this sector potentiate fertilization efficiency that facilitates fertilization of more females from a single collection. It had some limitation such as; to be developed it needs biomarker library and restrictions of purebred on artificial insemination [155].…”
Section: Sperm Nanopurificationmentioning
confidence: 99%
“…It was shown to exert cytotoxic and genetoxic damage in the testicular tissue in rats [75] and increased heat-shock protein 70 expression [76] suggesting high levels of cellular stress that may significantly affect subsequnt embryo development if these spermatozoa are used for fertilization. Titanium oxide was also toxic for buffalo sperm in vitro [77].…”
Section: Controversies In the Use Of Nanotechnology In Reproduction: mentioning
confidence: 99%
“…Nanotoxicity in buffalo bull spermatozoa has been reported earlier with titanium oxide (Pawar and Kaul, 2014). Braydich Stolle et al (2005) have demonstrated nanotoxicity with cadmium oxide, Ag NPs, molybdenum and aluminium nanoparticles in the mouse spermatogonial stem cells.…”
Section: Discussionmentioning
confidence: 56%